Long Non-coding RNAs and mRNAs Expression Profiles of Monocyte-Derived Dendritic Cells From PBMCs in AR - Zhou, Yumei; Chen, Xuemei; Zheng, Yanfei; Shen, Rongmin; Sun, Shuxian; Yang, Fei; Min, Jiayu; Bao, Lei; Zhang, Yan; Zhao, Xiaoshan; Wang, Ji; Wang, Qi (Frontiers in Cell and Developmental Biology, 2021)
Objective: The objective of this study is to explore the long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs) expression profiles of monocyte-derived dendritic cells (DCs) obtained from peripheral blood mononuclear cells (PBMCs). DCs are known to play a major role in the regulating function of allergic rhinitis (AR). Methods: PBMCs were separately isolated from the human peripheral blood of patients with AR and normal person (NP). The mixed leukocyte reaction (MLR) assay was used to evaluate the function of DCs. Flow cytometry was used to determine the immune regulatory function of immature DCs (imDCs) and mature DCs (mDCs). lncRNAs and mRNAs in the NP group (DCs isolated from NP) and the test group (DCs isolated from patients with AR) were identified via chip technology and bioinformatic analyses. Moreover, bioinformatic analyses were employed to identify the related biological functions of monocyte-derived DCs and construct the functional networks of lncRNAs and mRNAs that are differentially expressed (DE) in imDCs and mDCs. Results: MLR was significantly higher in the mDCs group than that in the imDCs group. CD14 was highly expressed in imDCs, whereas HLA-DR, CD80, and CD86 were highly expressed in mDCs (p < 0.001). We identified 962 DE lncRNAs and 308 DE mRNAs in the imDCs of NP and patients with AR. Additionally, there were 601 DE lncRNAs and 168 DE mRNAs in the mDCs in the NP and test groups. Quantitative RT-qPCR was used to study the significant fold changes of lncRNAs and mRNAs. The Kyoto Encyclopedia of Genes and Genomes analysis found 16 significant regulated pathways in imDCs and ten significant regulated pathways in mDCs, including the phagosome, cell adhesion signaling pathway, and inflammatory mediator regulation of TRP channels pathway. Conclusions: Our research studied the lncRNA and mRNA expression profiles of monocyte-derived DCs and demonstrated the functional networks that are involved in monocyte-derived DCs-mediated regulation in AR. These results provided possible molecular mechanisms of monocyte-derived DCs in the immunoregulating function and laid the foundation for the molecular therapeutic targets of AR.